PRODUKTIVITAS PADI PADA MUSIM PENGHUJAN DAN MUSIM KEMARAU DI WILAYAH DESA CIREBON GIRANG (Rice Productivity in The Rainy and Dry Seasons in The Cirebon Village Area) - Amran Jaenudin; E. Tadjudin; Meilina Parsetyo; Maryuliyanna Maryuliyanna (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2020)
This research aims to determine the appropriate rice cultivation and cropping patterns in the rainy and dry seasons and to find out the analysis of rice farming in the rainy and dry seasons. The time of the research is from January to April 2019. The research location was in the village of Cirebon Girang, Talun District, Cirebon. The method used in this research is descriptive qualitative. The results showed that rice cultivation in the rainy and dry seasons experienced differences especially in fertilization, different plant disturbing organisms, different cropping patterns from the two farmer groups, as well as the highest farming business analysis in the Talun Makmur Rainy Season Farmer group Rp. 22,772,885 and the lowest farming business is the Tanjung Makmur farmer group. Rainy season Rp. 17,044,044. While the large profits obtained in the Talun Makmur Rainy season farmers group of Rp. 24,718,667.